Takhrij and Syarah Hadith of Chemistry: Prohibition of Wearing Gold Rings for Men - Ahmad Syaefa Fadilah; Nunung Kurniasih; Nyimas Shoffah Shofiyatus Salamah; Wahyudin Darmalaksana; Agus Suyadi Raharusun (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad SAW. regarding the prohibition of wearing gold rings for men. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The results of this study are the reasons why men are prohibited from wearing gold rings, and the reasons why women are safe to wear gold jewelry from a medical perspective. The conclusion of this research is takhrij and syarah hadith of Rasulullah SAW. regarding the prohibition of wearing gold rings for men in a medical view that has pros and cons, as well as a social and economic perspective. Then it is compared with other types of preparations, namely cosmetics from gold extracts regarding the safety and Islamic views regarding the use of these cosmetics.